Kajian Faktor-Faktor Motivasi yang Berpengaruh terhadap Minat Berwirausaha pada Mahasiswa Program Studi Manajemen Fakulas Ekonomi Unika Widya Mandala Madiun - Srimulyani, Veronika Agustini (Widya Warta, 2014)
The purpose of this study is to analyze motivation factors which influence the interest in entrepreneurship. Those factors comprise risk tolerance, personal goal, and work freedom. In addition, this research also looks for the difference of interest of the students with different gender and parental background. It is an empirical study with the students of Management Department of Catholic University of Widya Mandala Madiun as its object. The respondent of this research is 55 in number. The data were analyzed making use of multiple linear regression analysis technique with SPSS software version 17. The result of the simultaneous test indicated that risk tolerance, personal goal, and work freedom had positive significant effect on the students’ interest in entrepreneurship. While, the result of the partial test showed that risk tolerance and personal goal had positive significant effect on the students’ interest in entrepreneurship. However, the interest in entrepreneurship, viewed from the students’ gender and parental background, was of no significant difference.